2019
DOI: 10.2478/hjbpa-2019-0027
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Corporate Mission Statements: From pursuing profit to distinctive and social value

Abstract: A mission statement has a significant meaning as the initial and essential step in a company’s strategic planning process. Previous studies have pointed out the necessity of monitoring and longitudinal study of corporate mission statements as they should be continuously revised against changes in companies’ strategies and business environment. This study aims to shed light on what types of strategies and values are currently highlighted in companies’ mission statements in comparison with the findings of a well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…The development of an enterprise is driven by the power of individuals. Therefore, in the selection and employment of talents, the professionalism of the human resources department is particularly important [ 21 ]. The human resources department should select personnel who meet the actual needs of the enterprise from the actual situation.…”
Section: Enterprise Business Management In the New Economic Environmentmentioning
confidence: 99%
“…The development of an enterprise is driven by the power of individuals. Therefore, in the selection and employment of talents, the professionalism of the human resources department is particularly important [ 21 ]. The human resources department should select personnel who meet the actual needs of the enterprise from the actual situation.…”
Section: Enterprise Business Management In the New Economic Environmentmentioning
confidence: 99%
“…Also, if stakeholders perceive an airline positively through strategic communication, the perceptions will be positively associated with the continuation and growth of its business and investor loyalty (Koehler and Hoffmann, 2018). Moreover, several studies found that there are positive correlations between companies' strategic communications and their financial performance (Pearce and David, 1987;Kohut and Segars, 1992;Seo and Itoh, 2019).…”
mentioning
confidence: 99%